Indazole versus indole-based cationic merocyanines with red shifted in-cellulo emission for selective mitochondria imaging. (February 2022) - Boujut, Margot; Chevalier, Arnaud; Schapman, Damien; Bénard, Magalie; Galas, Ludovic; Gallavardin, Thibault; Franck, Xavier
Abstract: Selective fluorophores are seminal for the development of fluorescent cell imaging allowing the simultaneous monitoring of several biological parameters. Mitochondria are one of the main targets of optical microscopy as their dynamics are related to many biological events. One of the best strategy to target them, is to design cationic dyes which accumulate preferentially in their membranes due to their high electrochemical potential. In this work, indazole scaffold was explored to build new cationic merocyanine dyes and compared with indole scaffold. This nitrogen heteroaromatic structure is still very uncommon in dyes chemistry; therefore, a lot has to be discovered about the effects of pH, solvent polarity and methylation in cyclic nitrogen on their optical properties. Finally, fluorescent imaging revealed that a red shift occurred in the emission of these molecules inside the mitochondria. Graphical abstract: Image 1 Highlights: Fluorescent indazole-based cationic merocyanines were developed to probe mitochondria and compared to their indole analogues. pH and viscosity response was studied. In vivo, these compounds featured a red-shifted emission. This red-shift was attributed to aggregation formation inside of mitochondria.